Dampak Kecanduan Game Online terhadap Kesehatan - Sri Atikah; Ria Angelina Jessica Rotinsulu; Anggun Sasmita; Atik Sunarmi; Meinita Wulansari (Jurnal Kabar Masyarakat, 2024)
Online game addiction is a major concern for society today. Even though there is a lot of research devoted to efforts to reduce the level of online game addiction, the lack of research discussing the prevention of online game addiction is still an issue. The aim of this activity is to explore various options for preventing online game addiction, especially among teenagers as a group that is vulnerable to this problem. Teenagers, as the age group that faces the most obstacles related to the use of online games, require special attention. Preventing online game addiction in teenagers is essential considering its impact covering health, psychological, academic, social and financial aspects in their lives. The importance of this service activity is to prevent the bad effects of online game addiction which can disrupt teenagers' lives. The hope is that this activity can make a significant contribution to efforts to prevent online gaming addiction, while supporting future research to explore broader prevention alternatives.